1998
DOI: 10.1046/j.1365-2133.1998.02462.x
|View full text |Cite
|
Sign up to set email alerts
|

Calcipotriol ointment in nail psoriasis: a controlled double-blind comparison with betamethasone dipropionate and salicylic acid

Abstract: This double-blind randomized study was designed to compare the efficacy and safety of calcipotriol ointment (50 microg/g) with betamethasone dipropionate (64 mg/g) and salicylic acid (0.03 g/g) ointment in the treatment of nail bed psoriasis. Fifty-eight patients applied the given drug to the affected nails twice a day for 3-5 months, depending on clinical response. Efficacy was assessed monthly on the basis of nail thickness, measured in millimetres. Photographs of the treated nails were taken at baseline, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
74
0
3

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(80 citation statements)
references
References 11 publications
(19 reference statements)
3
74
0
3
Order By: Relevance
“…Both treatments demonstrated similar levels of response in reducing subungual hyperkeratosis; however, only about half of the patients responded to treatment [17]. Rigopoulos et al confirmed the benefits of using topical calcipotriol in combination with a topical steroid cream in an open-label study utilising calcipotriol cream on weekdays and clobetasol propionate at weekends over 6 months.…”
Section: Conventional Treatment Approaches To Managing Nail Psoriasismentioning
confidence: 56%
See 1 more Smart Citation
“…Both treatments demonstrated similar levels of response in reducing subungual hyperkeratosis; however, only about half of the patients responded to treatment [17]. Rigopoulos et al confirmed the benefits of using topical calcipotriol in combination with a topical steroid cream in an open-label study utilising calcipotriol cream on weekdays and clobetasol propionate at weekends over 6 months.…”
Section: Conventional Treatment Approaches To Managing Nail Psoriasismentioning
confidence: 56%
“…A double-blind, randomised study compared the efficacy of twice-daily calcipotriol ointment with a combination of betamethasone dipropionate and salicylic acid ointment in 58 patients with nail psoriasis over 3 months [17]. Both treatments demonstrated similar levels of response in reducing subungual hyperkeratosis; however, only about half of the patients responded to treatment [17].…”
Section: Conventional Treatment Approaches To Managing Nail Psoriasismentioning
confidence: 99%
“…Calcipotriol twice daily for 3–6 months, either as monotherapy or in conjunction with topical corticosteroids, has been evaluated in the treatment of nail psoriasis in several studies [10,11,12], even though no study utilized the NAPSI to evaluate the results. In the population under study, the patients exhibited significant improvement of nail signs correlated with nail bed psoriasis (subungual hyperkeratosis, onycholysis, oil drop and pitting) using the two-compound formulation (fig.…”
Section: Discussionmentioning
confidence: 99%
“…A comparison of calcipotriol ointment with a combination of betamethasone dipropionate and salicylic acid ointment (Diprosalic) showed that calcipotriol was as effective as the combination product for treating nail psoriasis (Tosti et al, 1998). Comparisons of 0.005% calcipotriol ointment and 5% coal tar ointment in conjunction with sun exposure in 10 adult patients with stable plaque psoriasis showed that both calcipotriol and coal tar ointment had comparable efficacies in treating stable plaque psoriasis when used simultaneously with sun exposure, although the initial response to calcipotriol was faster (Kaur et al, 2001).…”
Section: Calcipotriol (Calcipotriene)mentioning
confidence: 99%
“…The calcipotriol cream is effective in treatment of plaque psoriasis and statistically significantly better than the placebo alone (Staberg et al, 1989). In addition, a solution has been developed for scalp psoriasis (Klaberg et al, 1994), and calcipotriol ointment has also been investigated for nail psoriasis (Tosti et al, 1998).…”
Section: Calcipotriol (Calcipotriene)mentioning
confidence: 99%